Visualizing the unfamiliar: ethnography of an emerging moment in Cairo - Schindler, Alexandra (AUC Knowledge Fountain, 2012)
This thesis explores the artwork and practices of visual artists as they negotiate the current political and historical moment in Cairo. This project tries to disrupt the binary of state versus market that has often been used as an analytical lens through which to understand Egyptian contemporary art. Instead, this thesis argues that, through a politics of the everyday, artists are exploring and challenging categories of revolution and the political. Nonetheless, regulatory frameworks, such as the language of neoliberal governance, continue to be reproduced within these subversive spaces and moments. This project considers what sorts of questions can be asked in an emerging moment, in which the language of the familiar and the unfamiliar is constantly shifting through changing processes and events. By theorizing an emerging moment, the purpose of this thesis is not to map any possible futures, but instead, to recognize the experimental processes and practices through which the interlocutors try to imagine an alternative future. This project considers what these practices mean for the gallery as an art space as well as alternative forms of organizing that emerge outside the gallery. Furthermore, this thesis explores the relationship between visual production and revolution. In a moment of â visual surplus,â artists struggle to negotiate their own visual art practices with the containing desires that emerge when revolution is imagined as a fixed and static category. In using the analytical lens of the everyday, this thesis questions what becomes legible as the political and what sorts of practices are thus rendered illegible by hegemonic language. This project also explores art spaces of community and collectivity as possible sites for artists to critically engage with the question of revolution as containment and to challenge hegemonic notions of art, the political and revolution. It serves primarily as an analytical space in which to explore this emerging moment and the different sites of resistance that artists traverse. The methodology of the thesis is meant to permit not only a flexibility in the theoretical framework but also to allow the initial questions of the project to fluctuate along with the interlocutors'.